Developing strategies "SATIA": How to manage dysphagia in older people? A Delphi panel consensus - Huafang Zhang; Li Zheng; Mengling Tang; Fanjia Guo; Lili Yang; Suxiang Liu; Jinyun Wang; Jie Chen; Chenxi Ye; Yajun Shi; Sihan Li; Wenfeng Xue; et al. (Wiley, 2023)
Abstract Aim To develop a set of evidence‐informed strategies to assist older people to improve swallowing functions and prevent further damage from complications. Design A two‐round Delphi survey. Methods An initial set of dysphagia care strategies with 74 relevant items for older people was formed based on a literature review by seven researchers. An online survey was conducted by 21 panellists, and data of experts' opinions were collected and analysed by improved Delphi method. Results The positive coefficients in the two rounds of expert consultation were 85.71% and 83.33%, respectively. Consensus was reached with 53 items included and was allocated into the following five sections: (1) screening, (2) assessment, (3) training, (4) interventions and (5) management. These strategies were named with the acronym of each section-"SATIA". The management strategy can be applied to guide the management of older people with dysphagia.